Trauma exposure, PTSD and indices of fertility - Rachel Wamser-Nanney (Taylor & Francis Group, 2020)
Background: Trauma exposure and posttraumatic stress disorder (PTSD) has been linked with numerous adverse health conditions, but it is unclear if trauma exposure and PTSD are associated with infertility. The objective of this study was to examine the contributions of trauma exposure and PTSD symptoms in predicting length of time to conception and utilization of infertility testing and treatment. Participants: Two hundred and forty-six trauma-exposed females (Mage = 36.69, SD = 10.82, Range = 19-59; 62.2% white) who had either been pregnant or had tried to become pregnant were included in the study. Participants' level of trauma exposure and PTSD symptoms were examined in relation to length of time to conception and use of infertility testing and treatments. Result(s): Infertility was present in 16.7% of the sample, 12.4% of participants had seen a doctor regarding infertility and 9.9% of participants had undergone fertility testing or treatments. PTSD was significantly related to longer length of time to conception, use of infertility testing and treatment and number of infertility testing and treatments, after controlling for covariates. Cumulative trauma, defined as number of traumatic exposures, was marginally related to use of infertility testing and treatments, but not to length of time to conception or number of infertility testing and treatments. Neither cumulative trauma nor PTSD was associated with self-reported infertility diagnosis. Conclusion(s): PTSD, but not trauma exposure, may be a risk factor for reduced fecundity and increased use of infertility treatment and testing among women.